Effect of natural and synthetic antioxidant on the quality of broiler meat during refrigeration - Masum, MMR; Mahmud, S; Liza, FA; Islam, MR; Azad, MAK; Rahman, MM (Meat Research, 2025)
This study evaluated the effects of natural and synthetic antioxidants and antimicrobial agents on the quality and shelf life of fresh and refrigerated chicken meat. Fresh chicken meat samples were divided into four treatment groups: T0 (control, no antioxidant), T1 (1% lemon peel extract), T2 (1% orange peel extract), and T3 (0.01% Butylated Hydroxytoluene, BHT). Samples were stored at 4°C for 9 days, and quality parameters were assessed at intervals of 0, 3, 6, and 9 days. Sensory attributes (color: L*, a*, b* values), proximate composition (dry matter, crude protein, ether extract, and ash), physicochemical properties (pH, water-holding capacity, drip loss, and cooking loss), biochemical stability (thiobarbituric acid reactive substances, TBARS), and microbial quality (total viable count, coliform count, yeast, and mold count) were analyzed. Instrumental color analysis showed that T3 had the highest L* (47.44) and a* (4.95) values, with peak redness (6.35) on day 9. Significant differences (P < 0.01) were observed in color attributes across treatments and storage periods. Proximate composition analysis revealed significant differences (P < 0.01) among treatments. T3 exhibited the highest dry matter (DM) and ash content, while T1 had the highest crude protein (CP) content. Ether extract (EE) values were most favorable in T3. Physico-chemical properties indicated significant differences (P < 0.01) in pH, water-holding capacity (WHC), drip loss, and cooking loss. T1 had the most favorable pH (5.72–5.88), while WHC was highest in T3 (92.05%–93.22%). Biochemical analysis showed TBARS values significantly increased (P < 0.01) over time, indicating lipid oxidation. TBARS values ranged from 0.193 to 0.226 across treatments, with T3 exhibiting the lowest values, signifying better oxidative stability. Microbial analysis confirmed that T3 had the lowest total viable count (5.43 log CFU/g), coliform count (2.85 log CFU/g), and yeast-mold count (2.60 log CFU/g), demonstrating its superior antimicrobial effectiveness. Overall, 0.01% BHT (T3) was the most effective antioxidant and antimicrobial agent, preserving meat quality and extending shelf life under refrigerated conditions (4 ± 1°C).